2017
DOI: 10.3892/ol.2017.5834
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and prognostic factors of resected pancreatic neuroendocrine neoplasms: A single-center experience in China

Abstract: Abstract. The aim of the present study was to investigate the clinical, pathological and prognostic characteristics of Chinese patients with resected pancreatic neuroendocrine neoplasms (p-NENs). Data from patients who were surgically treated and pathologically diagnosed with p-NENs at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…In clinical practice, grade 2 NETs form a very heterogeneous group and survival in this group can be very different between a "low" grade 2 with a Ki67 close to 2% or a "high" grade 2 with a Ki67 close to 20%. In our study, a cut off of 5% turned out to be more relevant than a cut off of 2% for Ki67, which has already been suggested (3,6,23). The WHO classification of NET should therefore probably be revised.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In clinical practice, grade 2 NETs form a very heterogeneous group and survival in this group can be very different between a "low" grade 2 with a Ki67 close to 2% or a "high" grade 2 with a Ki67 close to 20%. In our study, a cut off of 5% turned out to be more relevant than a cut off of 2% for Ki67, which has already been suggested (3,6,23). The WHO classification of NET should therefore probably be revised.…”
Section: Discussionmentioning
confidence: 58%
“…Survival and prognostic factors analysis of 151 intestinal and pancreatic neuroendocrine tumors: a single center experience Tumor grade, stage, degree of differentiation, and primary tumor size, are well recognized as prognostic factors in NETs. Other factors related to poorer prognosis have been suggested like advanced age at diagnosis, pancreatic tumor localization, the presence of synchronous metastases, and functional character of the tumor, but are still discussed (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Tumor grade, evaluated according to the 2006 ENETS classification based on two proliferative markers [mitotic index (MI) and Ki67 labeling index], is considered the major prognostic factor.…”
Section: Original Articlementioning
confidence: 99%
“…However, whether it is an prognostic factor has always been conflicting, as different investigations giving different results14 . A number of studies reported that lymph node status had important prognostic value9,23,24,25,26. However, other reports failed to detect a survival difference in those with lymph node diseases27,28,29.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour size is a readily available parameter, can be accurately measured and has the great advantage of little discrepancy among observers. Its prognostic value in PNETs has been investigated extensively 8,9,10,30,31,32,33. Although the results beween different studies were inconsistent, tumour size was used as a criterion of staging in the AJCC and ENETS system6,7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation